Harnessing beliefs to optimally disclose contestants' types - Marco Serena (Economic Theory, 2021)
A contestant's effort depends on her knowledge of her rival's type. This knowledge is often limited in real-life contests. We propose a model where the principal of a contest has commitment power to verifiably disclose contestants' types. We investigate the optimal disclosure policy to stimulate contestants' efforts. Full disclosure stimulates more (less) effort than full concealment if high-types are more (less) likely than low-types. However, regardless of the likelihood of types, the optimal policy is that of contingent disclosure; it is optimal to commit to disclosing if both contestants are high types and concealing otherwise.
Keywords: C72; D82; 330; Contests; Strategic complements; Strategic substitutes; Information